2017
DOI: 10.1111/apt.14108
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: interventions for abdominal pain management in inflammatory bowel disease

Abstract: Few interventions have been tested for IBD abdominal pain. The limited evidence suggests that relaxation and changing cognitions are promising, possibly with individualised dietary changes. There is a need to develop interventions for abdominal pain management in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 64 publications
0
65
0
Order By: Relevance
“…A systematic review of interventions that are not diseasemodifying found limited evidence suggesting that relaxation and behavioral stress management programs may be promising in reducing IBD abdominal pain. 49…”
Section: Health Care Maintenancementioning
confidence: 99%
“…A systematic review of interventions that are not diseasemodifying found limited evidence suggesting that relaxation and behavioral stress management programs may be promising in reducing IBD abdominal pain. 49…”
Section: Health Care Maintenancementioning
confidence: 99%
“…Alternatively, pain may be used to attract more of their doctor's attention to other symptoms. To improve the correlation of this measure, we could consider collecting additional information that may be associated with abdominal pain (i.e., disability, stress, sleep quality, fatigue) [30][31][32] because the question might be whether abdominal pain reflects a cause or a consequence of other symptoms.…”
Section: Two Previous Studies Conducted By Bennebroek Evertsz Et Almentioning
confidence: 99%
“…Patients described this cycle as having a significant impact on emotional and physical functioning and acting as a key barrier to effective communication and management of pain. The breadth of strategies used among participants reinforces the lack of a clear consensus around optimal pain management in IBD, as supported by prior research finding a wide variety of interventions for abdominal pain in IBD (9).…”
Section: Discussionmentioning
confidence: 83%
“…Others found that medication did not reduce their pain symptoms at all: "I generally don't use paracetamol or ibuprofen for the pain, because I don't feel that they work for me" (9).…”
Section: Iii) Medication Concernsmentioning
confidence: 99%